أهمية البعد الجيواقتصادي في علاقات الصين اتجاه افريقيا - ديلمي سلمى; بن عمر عادل (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2023)
تتبنى الصين عدة إستراتيجيات لتحقيق التفوق والتقدم، ومن أهمها الاستراتيجية الجيواقتصادية، والتي تعني التوجهات ذات الصبغة الاقتصادية خاصة التجارية التي تنتهجها الدول في إطار سياستها الهادفة لحماية اقتصادها الوطني عن طريق التحكم في الاقتصاد والأسواق العالمية، وتدرس الجيواقتصادية العلاقة بين الأرض والمعطيات الاقتصادية ومدى تفاعلها وآثارها على المستويات المحلية والاقليمية والدولية. وفي إطار دراستنا سوف نركز على الأهمية الجيواقتصادية في علاقات الصين اتجاه افريقيا، خاصة وأن افريقيا تعتبر سوقا ضخما بالنسبة لها. الكلمات المفتاحية: الجيواقثتصادية؛ الصين؛ افريفيا؛ Abstract: China adopts many strategies in order to advance and achieve development, among which are geoeconomic strategies, which refer to the economic orientations, notably trade-related ones that the country follows in the framework of its policy that aims at protecting its national economy. The protection of the latter is done through controlling economic and international markets. Geoeconomy generally studies the link between land and the economic data, and the extent of its interaction and impact locally, regionally, and internationally. In our study, we will focus on the geoeconomic importance of China’s relations with Africa, notably that the latter is considered to be a huge market for China